How to attend to screens? : Technology, ontology and precarious enactments - Ziewitz, Malte (STS Encounters, 2011)
In this paper, I explore the question of how to attend to screens. Starting from the puzzling observation that screens seem both ubiquitously present and conspicuously absent in everyday life, I find that existing studies tend to take the analytic status of screens for granted and juxtapose them with a human user to theorize the relationship between the two. In an attempt to avoid such dualisms, I turn to recent work in Science and Technology Studies (STS) and focus on how screens are being enacted in practice. However, exploring a strategy of enactment in the context of a recent ethnography of webbased patient feedback produces mixed results. Perhaps most importantly, the salience of objects is not given in enactment, but itself contingently accomplished - a process in which the role of the researcher is easily overlooked. The paper concludes that a call to attend to screens as ‘objects of interest’ may thus be better understood as an invitation to engage with people and things in situations in which the notion of ‘screens’ may (or may not) provide a useful heuristic for orienting inquiry.